The effect of the social and labour plan on addressing gender equity in selected mining houses in Lephalale - Masemola, Mathews Malegole (University of Limpopo, 2017)
This study looked into the effectiveness of the Social and Labour Plan on addressing the gender equity in selected mining houses in Lephalale. The newly elected democratic government of South Africa introduces numerous strategic policies to open all sectors of economy for all South Africans, but with special emphasis on the historically disadvantaged, which include women and people with disability as part of its economic emancipation policy. Hence the Social and Labour Plan was adopted. The main aim of the study was to investigate the effect of the Social and Labour Plan (SLP) in selected mining houses in Lephalale. A qualitative approach was used for this study, and interviews were contacted to collect data and thematic analysis used to analyse the data. It was found that the Social and Labour Plan (SLP) in the mines was not working fully and effectively. Also the research findings included, among others slow implementation of policies, more males than females, white male dominance, and discrimination of women, transformation, where taking place both on race and gender, only at snail pace and the lack of enforcement for implementation of policies such as the Social and Labour Plan (SLP) by the Department of Miners and Resources (DMR). Amongst other revelations were inequality issues, discrimination and nepotism experienced by women. Based on the finding the researcher recommended that mining organisations should review their mining Social Labour Plan (SLP) so that they state very clearly the number of women to be employed by the organisations, and such document once approved by the Department of Mineral Resources (DMR), should be complied to. Furthermore the Department of Mineral Resources (DMR) should commit to an annual review of the Social and Labour Plan Report performance by mining companies, instead of waiting for five years.
Thesis (MBA.) -- University of Limpopo, 2017
Keywords: Labour plan; gender equity; Democracy; Women; Gender equity; Woment in development - South Africa